The aetiology and pathogenesis of rectal prolapse - Joshi, H (2016)
It is still an enigma that some patients develop rectal prolapse whilst others with similar risk factors do not. Biomechanical assessment of the skin may provide further insight into the aetiology of this complex condition. Components of connective tissue other than collagen have been found to be involved in patients with rectal prolapse. Elastin fibres are an abundant and integral part of many extracellular matrices and are especially critical for providing the property of elastic recoil to tissues. The significance of elastin fibres is clearly reflected by the numerous human conditions in which a skin phenotype occurs as a result of elastin fibre abnormalities. The organization of elastic fibres differs between controls and subsets of patients with rectal prolapse, and their importance for maintaining the structural and functional integrity of the pelvic floor has been demonstrated in transgenic mice, with animals which have a null mutation in fibulin-5 (Fbln5¡/¡) developing prolapse. This study aimed to compare fibulin-5 expression in the skin of patients with and without rectal prolapse. Between January 2013 and February 2014, skin specimens were obtained during surgery from 20 patients with rectal prolapse and from 21 without prolapse undergoing surgery for other indications. Fibroblasts from the skin were cultured and the level of fibulin-5 expression was determined on cultured fibroblasts, isolated from these specimens by quantitative real-time polymerase chain reaction. Immunohistochemistry was performed on fixed tissue specimens to assess fibulin-5 expression. Orcein staining measured expression levels of elastin in the skin, and Image J. Tensile tests were performed using the Zwick Roell device, with custom ceramic clamps. For statistical analysis, Student's t test was used. Fibulin-5 mRNA expression and fibulin-5 staining intensity were significantly lower in young male patients with rectal prolapse compared with age matched controls [fibulin-5 mean _ SD mRNA relative units, 1.1 _ 0.41 vs 0.53 _ 0.22, P = 0.001; intensity score, median (range), 2 (0–3) vs 1 (0–3), P = 0.05]. There were no significant differences in the expression of fibulin-5 in women with rectal prolapse compared with controls. Histological analysis of prolapse vs control showed percentage dermal elastin fibres of 9 vs 5.8 % (p=0.001) in males and 6.5 vs 5.3 % (p=0.05) in females. Patients with more severe prolapse (external) had a significantly (p=0.05) higher percentage dermal elastin fibres 6.9 vs 6.1 % than internal prolapse. Young's modulus of patients with prolapse was lower in males (3.3 vs 2.8, p=0.05) and females (3.1 vs 2.7, p=0.05). Patients with prolapse have a higher concentration of elastin fibres in the skin, and these differences are quantitatively demonstrated through mechanical testing. This suggests that the aetiology may be a result of a dysfunction of elastin fibre assembly. Fibulin-5 may be implicated in the aetiology of rectal prolapse in a subgroup of young male patients.